Analisis Peranan Perpustakaan dalam Menumbuhkan Minat Baca Siswa MTs Negeri 3 Klaten - Khairullah, Imam Arwani; Saufa, Arina Faila; Ma’arif, Achmad Syafi’I; Septiawan, Tegar Adi; Nuraini, Nuri; Salma, Shofiyyah (Jurnal Tadwin, 2021)
The school library is an important facility in fostering and fostering student interest in reading in the school environment. Therefore, the role of the library is needed to facilitate the information needs of students. The purpose of this study was to determine the reading interest of the students of MTs N 3 Klaten and what efforts were made by the library in growing students' interest in reading. Researchers use a qualitative approach to get a natural picture or description of the theme being studied. The main data sources for researchers were obtained through observation, interviews and documentation in the form of library visit books in November 2021. The results showed that students visited the library more in the 2nd week, students visited the library more for the purpose of borrowing books and the types of books they used. Most borrowed books are general works. The MTs N 3 Klaten library also makes various efforts to increase students' reading interest, namely through several activities, such as 1) scheduling regular rotating visits for each class, 2) giving rewards or prizes to students who are the most active in visiting the library, 3) displaying student works in the library, and 4) collaborating with teachers to create activities based on the use of library services.